2020
DOI: 10.1016/j.neuropsychologia.2020.107683
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a functional reorganization in the auditory dorsal stream following unilateral hearing loss

Abstract: Unilateral hearing loss (UHL) generates a disruption of binaural hearing mechanisms, which impairs sound localization and speech understanding in noisy environments. We conducted an original study using fMRI and psychoacoustic assessments to investigate the relationships between the extent of cortical reorganization across the auditory areas for UHL patients, the severity of unilateral hearing loss, and the deficit in binaural abilities. Twenty-eight volunteers (14 UHL patients) were recruited (twenty-two fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 80 publications
4
36
0
Order By: Relevance
“…However, findings are scarce regarding how the observed neuroplasticity in asymmetric hearing is related to binaural auditory performance, such as sound localization ability. In one recent fMRI study of subjects with varying degrees of asymmetric hearing loss ( Vannson et al, 2020 ), changes in auditory localization ability were associated with neural plasticity in the posterior auditory cortex, where structural correlation with localization performance was also observed in this study. Neuroimaging studies with sound localization tasks have not yet been reported, and neuroplasticity related to auditory spatial performance changes should be further elucidated with consideration of clinical variables such as the degree, duration, and onset of hearing asymmetry.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…However, findings are scarce regarding how the observed neuroplasticity in asymmetric hearing is related to binaural auditory performance, such as sound localization ability. In one recent fMRI study of subjects with varying degrees of asymmetric hearing loss ( Vannson et al, 2020 ), changes in auditory localization ability were associated with neural plasticity in the posterior auditory cortex, where structural correlation with localization performance was also observed in this study. Neuroimaging studies with sound localization tasks have not yet been reported, and neuroplasticity related to auditory spatial performance changes should be further elucidated with consideration of clinical variables such as the degree, duration, and onset of hearing asymmetry.…”
Section: Discussionsupporting
confidence: 74%
“…However, findings are scarce regarding how the observed neuroplasticity in asymmetric hearing is related to binaural auditory performance, such as sound localization ability. In one recent fMRI study of subjects with varying degrees of asymmetric hearing loss (Vannson et al, 2020), changes in auditory localization ability were associated with neural plasticity in the posterior auditory cortex, where structural correlation with localization performance was also observed in this study.…”
Section: Gray Matter Volume In the Posterior Part Of The Auditory Cortex Is Associated With Auditory Spatial Abilities In Right Single-sisupporting
confidence: 79%
“…Using the mismatch negativity evoked by infrequent changes in sound location, Sonnadara et al (2006) found a longer latency in the positive peak in response to a large angle (90 • ) compared to a smaller one; they also alluded that this can be partially interpreted by applying the spatial channel theory suggested by Boehnke and Phillips (1999) who posited that 0 and 30 • are processed in the same spatial channel whereas 0 and 90 • (angles larger than 30 • ) are not. Moreover, according to the theory, spatial location information belonging to different channels is not processed in the lower level of the auditory system but rather in the higher order auditory cortex (Vannson et al, 2020). In this sense, the prolonged latency at the greater azimuth angles could be associated with the precise spatial processing properties of the central auditory system for between-channel discrimination.…”
Section: Hemispheric Asymmetry In Unilateral Deafnessmentioning
confidence: 99%
“…For example, the findings from a recent study show a significant inverse relationship between speech perception ability, the duration of deafness, and cortical N1 responses in right-sided unilateral deafness, indicating that substantial neural plasticity occurs due to deafness in the right ear (Cañete et al, 2019). Similarly, a recent fMRI study also showed that a stronger dominance shift to the hemisphere ipsilateral to the better ear is significantly related to poorer horizontal sound localization in people with unilateral hearing loss (Vannson et al, 2020). Thus, the primary goal of this study is to determine whether electrophysiology can predict the behavioral perceptual ability of sound localization in UD adults.…”
Section: Introductionmentioning
confidence: 96%
“…In addition, the intensity was equalized according to the root mean square level. The vocal and nonvocal stimuli used in this study originated from the database exploited in previously published studies (Belin et al, 2000; Massida et al, 2011; Vannson et al, 2020). They comprised speech stimuli and nonspeech vocal stimuli (e.g., laughs, coughs) and environmental sounds, including sound alarms, car horns, streaming water, animal vocalizations, etc.…”
Section: Methodsmentioning
confidence: 99%